Determination of trace elements in serum samples by isotope dilution inductively coupled plasma mass spectrometry using on-line dialysis - Gine, M. F.; Bellato, ACS; Menegario, A. A. (Royal Soc Chemistry, 2004)
An on-line dialysis flow system coupled to inductively coupled plasma mass spectrometry to determine trace elements in serum samples by isotope dilution is presented. Isotope dilution was performed on samples incubated with enriched Cu-65, Zn-66, Se-77 and Pb-206 for 24 h at 36degreesC prior to dialysis to quantified total element concentrations. The sample and acceptor solutions flowed through the dialysis unit with cellophane membrane placed in between the compartments. The serum sample (1 mL) was left to recycle in a closed path while the acceptor solution was continuously pumped along the dialyzer channel and through a cationic AG50W X-8 resin column. After 10 min, around 70% of Na, K and Cl migrate from the sample. Three replicate injections of 0.1 mL were performed for the clean sample after each separation step. The on-line coupling of the dialyzer to ICP-MS allowed isotope dilution for total element determination either in the cleaned sample or by eluting the cations retained in the resin to be carried out. Results demonstrated no matrix effects from alkaline elements or spectral interference from ArNa+ on Cu-63, ArCl+ on Se-77 and (SO2+)-S-34 on Zn-66. The precision of isotope ratio measurements for Cu and Zn was around 1% and for Se and Pb was around 2.5%. The values found for the reference serum sample IMEP-17 were in good agreement with the certified values for Cu, Zn and Se.